KNEE ISOKINETIC TORQUE IMBALANCE IN FEMALE FUTSAL PLAYERS - Rodrigues,Ana Carolina de Mello Alves (2017)
ABSTRACT Introduction: The specificity of sports training can lead to muscle specialization with a possible change in the natural hamstring/quadriceps torque ratio (HQ ratio), constituting a risk factor for muscle injury at the joint angles in which muscle imbalance may impair dynamic stability. Objective: The aim was to evaluate the torque distribution of the hamstrings and quadriceps and the HQ ratio throughout the range of motion in order to identify possible muscle imbalances at the knee of female futsal athletes. Methods: Nineteen amateur female futsal athletes had their dominant limb HQ ratio evaluated in a series of five maximum repetitions of flexion/extension of the knee at 180°/second in the total joint range of motion (30° to 80°). The peak flexor and extensor torque and the HQ ratio (%) were compared each 5° of knee motion using one-way repeated measures ANOVA and Tukey’s post hoc test (p<0.05) to determine the joint angles that present muscular imbalance. Results: Quadriceps torque was higher than 50° to 60° of knee flexion, while hamstrings torque was higher than 55° to 65°. The HQ ratio presented lower values than 30° to 45° of knee flexion and four athletes presented values lower than 60%, which may represent a risk of injury. However, the HQ ratio calculated by the peak torque showed only one athlete with less than 60%. Conclusion: The HQ ratio analyzed throughout the knee range of motion allowed identifying muscle imbalance at specific joint angles in female futsal players.